Calorie and time-restricted feeding improves liver and kidney histopathology in streptozotocin-induced type 1 diabetic rats - Taufani, Indra Putra; Laila, Sri Rahmatul; Tasminatun, Sri; Simaremare, Sailent Rizki Sari; Mardiana, Meity; Situmorang, Jiro Hasegawa (Frontiers in Physiology, 2025)
Type 1 diabetes (T1D) is associated with severe metabolic dysregulation and organ complications such as hepatomegaly and nephropathy. While insulin therapy remains the cornerstone of treatment, there is growing interest in dietary interventions that modulate metabolic outcomes independently of insulin. This study aimed to investigate the effects of calorie restriction (CR) combined with time-restricted feeding (TRF) on metabolic and histological parameters in a high-fat diet-fed, streptozotocin-induced rat model of T1D. Male Sprague-Dawley rats were divided into control, diabetic, and two CR-TRF groups (day-fed and night-fed). CR-TRF groups received 70% of the diabetic group’s caloric intake during either the light or dark phase. Body weight, fasting glucose, oral glucose tolerance test (OGTT), triglycerides, water intake, and calorie intake were measured. Liver and kidney tissues were evaluated using H&E and Cason’s Trichrome staining. Although CR-TRF did not significantly improve body weight, both interventions markedly reduced water intake and improved hepatomegaly. OGTT results showed improved slight glycemic responses in CR-TRF groups, particularly in the day-fed group. Diabetic rats exhibited liver and renal damage, which were significantly attenuated by CR-TRF. Histological analysis revealed preserved tissue architecture and reduced vacuolation in both liver and kidney under CR-TRF conditions. These findings support the potential of calorie restriction, regardless of feeding time as adjunct therapies for T1D and warrant further exploration in translational models.